Early Detection of Anastomotic Leak via the Drain/Serum Amylase Ratio in Patients Undergoing Colorectal Surgery, Particularly in Ileal Anastomosis - Lee, Jong Min; Lee, Jeehye; Kim, Taehyung; Kim, Nam Kyu (Yonsei medical journal, 2025)
A high index of suspicion is crucial for early anastomotic leak (AL) diagnosis, enabling timely intervention and conservative management. Although recent studies have highlighted the potential of drain amylase (dAmy) as a predictive marker for AL, its application in colorectal surgery remains underexplored. A retrospective study was conducted among patients who underwent colorectal resection between March 2020 and November 2023. A total of 299 patients with at least one dAmy and serum amylase (sAmy) measurement between postoperative days 1 to 5 were included, after excluding patients with fecal diversion. Multiple logistic regression identified the drain/serum amylase ratio (d/s Amy) as an independent predictor of AL (odds ratio 1.032, 95% confidence interval 1.009-1.056; =0.007). The receiver operating characteristic curve demonstrated significant diagnostic ability for AL [area under the curve (AUC)=0.691], with a cut-off value of 2.54, a sensitivity of 48.4%, and a specificity of 94.2%. Patients with d/s Amy ≥2.54 had a significantly higher incidence of AL with a faster diagnosis compared to conventional methods (3.5 days vs. 5 days, =0.006). In patients who underwent ileal anastomosis, the d/s Amy ratio had an AUC of 0.936, with a sensitivity of 87.5% and a specificity of 96.6%. The postoperative d/s Amy ratio is valuable for early AL detection in patients undergoing colorectal surgery, particularly in those with ileal anastomosis. This simple and noninvasive test can aid in timely diagnosis, offering earlier intervention compared with conventional methods.